Verification of an agent model for chronic fatigue syndrome - Ab. Aziz, Azizi; Ahmad, Faudziah; Che Pa, Noraziah; Mohd Yusof, Shahrul Azmi (AICIT, Korea, 2013)
Chronic fatigue syndrome (CFS) is a disorder that is caused by multiple factors. Much work has been conducted to understand CFS mechanisms but little attention has been paid to model the behaviour of a person who experienced chronic fatigue syndrome. The article aims to present verification results made on an agent model that was developed to simulate the dynamics of CFS under the influence of stressful events and related personal profiles. The model developed earlier combines ideas from research in affective disorder, prevention medicine, artificial intelligence, and dynamic modeling.These ideas are encapsulated to simulate how a person is fragile towards stressors, and further develops a CFS condition.The model contains eight main components that interacts each other to simulate temporal dynamics in CFS. These are predisposed factors, stressors, viral infection, demand, stress, exhaustion, fatigue and immune function.In order to verify the model, two approaches namely; mathematical verification and logical verification were used to check whether the model indeed generates results that adherence to psychological literatures.